(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The results of studies on the production of zinc nitrate from waste zinc catalysts are presented. The waste zinc catalysts contains 74.55 % ZnO. The influence of technological factors on the degree of zinc extraction from the waste zinc catalysts by nitric acid has been investigated. The optimal parameters of the process have been determined. The maximum degree of zinc extraction is observed at an acid rate of 120%, and a nitric acid concentration of 30%. An increase in the duration of the process from 1 to 3 hours increases the degree of zinc extraction from 25.47% to 91.18% with other constant parameters. An increase in temperature from 55 to 95℃ contributes to an increase in the degree of zinc extraction to 91.18%.